Statistical Background of the Crisis of 1857 - Cole, Arthur H. (The Review of Economics and Statistics, 1930)
ECONOMIC surveys of the United States in the pre-Civil-War period never fail to make note of the revulsion of business which came in the year I857. Sometimes this is indicated as the culmination of a speculative movement of considerable, though uncertain, duration. Sometimes it is spoken of as a peculiar, almost quixotic, affair, deriving immediately from the failure of the Ohio Life Insurance and Trust Company, just as the of i837 is alleged to have flowed directly from the single cause of the famous Specie Circular. Again, where such accounts make allowance for speculative activity as forerunner of the debacle of I857, the chief generative element of this speculation is held to have been the enlargement of gold supplies after the discoveries of the mid-century. Yet little has heretofore been accomplished in the scientific appraisal of business conditions in these years, and in particular little has been done in attempting to array together the several aspects of business experience with the object of discovering the various interrelations of these elements. An important exception to the first statement would be W. L. Thorp's Business Annals; but as his study is non-statistical in character, it lacks close comparability with that here undertaken. In the belief that greater realism may be given the crisis of I857 by the procedure just mentioned, certain data on the volume of trade, and on banking and finance, are here joined to those whiclh have been presented elsewhere upon the course of commodity prices, common stock values, and public land sales; and an effort is now made to reveal some of the differences in these several movements.1 THE VOLUME OF TRADE